Structural Characterization and Electrical Properties of Barium Titanate Nanorod Crystals Synthesized via Hydrothermal Methods - Mubarak Hamad Oglah (Tikrit Journal of Pure Science)
Barium titanate nanorods (BTNRs) were formed via the hydrothermal process through preliminary preparation of a slurry of hydroxide precursors by mixing BaCl2.H2O and TiCl2 with a (10 Molar) of NaOH solution. The hydroxide slurry was heated at (205 °C) for (24 h) to complete the process. This study focused on examining the electrical properties of nanoscale barium titanate (BaTiO3) synthesized via the hydrothermal technique. Scanning Electron Microscopy (SEM) imaging demonstrated the unique rod-like shape of barium titanate nanorods, confirming their production. Furthermore, X-ray diffraction (XRD) analysis confirmed the crystalline structure attained under the experimental circumstances and confirmed the successful production of the BaTiO₃ perovskite phase. Fourier Transform Infrared Spectroscopy (FTIR) was utilized to identify the functional groups present in the nanomaterial. Additionally, the structure and composition of BaTiO3 were confirmed using Energy Dispersive Spectroscopy (designed as EDS). The electrical conductivity was assessed utilizing the four-point probe (4-point electrical conductivity) method to determine sheet resistance, while impedance spectroscopy was used to investigate the capacitance, and dielectric constant. The results revealed the intrinsic properties of BaTiO3 nanorods, highlighting its potential applications in electronics and capacitors.